Christianity and American democracy - Heclo, Hugh.; Bane, Mary Jo.; Kazin, Michael, 1948-; Wolfe, Alan, 1942- (Cambridge, Mass. : Harvard University Press, 2007)
Christianity, not religion in general, has been important for American democracy. With this bold thesis, Heclo offers a panoramic view of how Christianity and democracy have shaped each other over the years, and how their relationship is changing in the present day. Responding to his challenging argument, Mary Jo Bane, Michael Kazin, and Alan Wolfe criticize, qualify, and amend it. The result is a lively debate about a momentous tension in American public life.
Christianity and democracy in America / Hugh Heclo -- Democracy and Catholic Christianity in America / Mary Jo Bane -- Pluralism is hard work, and the work is never done / Michael Kazin -- Whose Christianity? Whose Democracy? / Alan Wolfe -- Reconsidering Christianity and American democracy / Hugh Heclo.
Includes bibliographical references (pages 243-283) and index.
Print version record.
In English.
Master record variable field(s) change: 072
Keywords: Democracy -- Religious aspects -- Christianity; Christianity and politics -- United States; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Christianity and politics; Democracy -- Religious aspects -- Christianity; United States; Christianity and politics; Political Science, other; Political Science; Social Sciences; Theologie, Christentum; POLITICAL SCIENCE / Political Ideologies / Democracy; Electronic books